The Correlation between the Numerical Status of Th22 Cells and Serum Level of IL-22 with Severity of Ulcerative Colitis - Abbas Arj (Iranian Journal of Allergy, Asthma and Immunology, 2018)
Ulcerative colitis (UC) is a chronic relapsing inflammatory bowel disease, yet its etiology as well as pathogenesis remain poorly understood. There is increasing evidence that aberrant expression of CD4+T lymphocytes plays an essential role in the progression of different pathologies such as UC. This study aimed to evaluate the circulatory frequency of T-helper 22 (Th22), a subset of CD4+ T cells, and serum level of its signature cytokine, IL-22, in patients with UC. Blood samples from 30 patients with UC and 30 controls (n=30) were tested for IL-22 level and circulatory Th22-cell count by ELISA and Flow cytometric analysis, respectively. Our results revealed higher serum level of IL-22 as well as circulatory frequency of Th22 cells in patients with UC compared to those in healthy controls. Notably, effective factors on severity of the disease were age, Th22, IL-22, ESR and CRP. We conclude that elevated circulating Th22 cells and their signature cytokine, IL-22, may be implicated in the pathogenesis of UC. These findings may provide preliminary experimental clues for the development of new therapies for UC and its severity judgment.